Child Safety Series: Poison Prevention - Bradshaw, Michael H. (My University, 1998)
Publication describes how to prevent children from being accidentally poisoned by medicine and household products.
MF645_1998_05
Keywords: MF645; Health and Saftey; Home and Family; MF